Islamic Work Ethics as a Strategic Resource: Integrating Dynamic Capabilities and Marketing Adaptability to Enhance Muslim Family-Owned Micro-Business Performance - Hasbullah, Judistira; Supratikno, Hendrawan; Bernarto, Innocentius (International Review of Management and Marketing, 2026)
Despite growing interest in Islamic Work Ethics (IWE), limited empirical evidence explains how ethical values enhance organizational capabilities and business performance among Muslim family-owned micro enterprises. This study develops and tests an integrated framework linking Islamic Work Ethics, Innovation Capability, Workforce Agility, and Marketing Mix Adaptability to Muslim Family-owned Micro-Business Performance. Unlike previous studies, Islamic Work Ethics is conceptualized as a multidimensional strategic intangible resource embedded within Indonesia’s socio-cultural context and integrated with Dynamic Capability Theory to explain how ethical values are transformed into organizational capabilities. Survey data were collected from 76 Muslim family-owned micro enterprises affiliated with the OK OCE entrepreneurial community in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Islamic Work Ethics positively influences Innovation Capability and Workforce Agility, while Workforce Agility significantly enhances both Innovation Capability and Marketing Mix Adaptability. Innovation Capability, Workforce Agility, and Marketing Mix Adaptability positively affect business performance, whereas the direct effect of Islamic Work Ethics on Marketing Mix Adaptability is insignificant. The study contributes by proposing a multidimensional Islamic Work Ethics measurement framework and demonstrating that culturally embedded ethical values strengthen dynamic capabilities, thereby promoting the sustainability and competitiveness of Muslim family-owned micro enterprises.